Fiscalização de contratos administrativos na Universidade Federal do Ceará - Silva, Maria de Jesus Lopes (2015)
The scope of the public interest is not realized only through the steps of planning, bidding and contracting. You get to the point to carry out the contract and under the legal aspect, the public administrator must designate server to monitor their implementation. The supervision functions as guarantor mechanism of best execution of the contract and fidelity to its object, and ensure compliance with the principle of efficiency in public administration. This study aims to analyze the supervision of administrative contracts of continuous nature, in the period 2012-2014, the Universidade Federal do Ceará. The theoretical approach is based on the process of the concepts of the Brazilian public procurement and its phases of administrative contracts and their characteristics and management and supervision of contracts, focused on the role and responsibilities of tax. It is characterized as descriptive research with qualitative approach and case study, done with bibliographic support, documentary and field. The research instrument was used questionnaire, which was applied to tax and former tax administrative contracts continuing nature of the institution. The results show that the UFC manager rightly chose the executive agent of the contract, however, he lacks administrative support, knowledge and the application of standardized instruments of surveillance and especially training and capacity building.